ELECTRICAL UNIT AND ASSOCIATED ADDITIONAL FUNCTIONAL MODULE - KRAEMER, Jacques; NOEL, Pascal (2019)
The subject matter of the present invention is an electrical unit (1) for an electrical installation that is capable of and intended for being connected to an electrical network, comprising at least: a primary functional module (2) that is capable of and intended for performing a current-switching function; an additional functional module (5) for performing at least one function requiring an electrical power supply, which electrical unit (1) is characterized in that the function of the additional functional module (5) is a function requiring an electrical power supply with the exception of a lighting function. La présente invention a pour objet un appareillage électrique (1) pour une installation électrique apte et destiné à être relié à un réseau électrique, comprenant au moins: un module fonctionnel primaire (2) apte et destiné à effectuer une fonction d'interruption du courant, un module fonctionnel additionnel (5) pour effectuer au moins une fonction nécessitant une alimentation électrique, appareillage électrique (1) caractérisé en ce que la fonction du module fonctionnel additionnel (5) est une fonction nécessitant une alimentation électrique à l'exclusion d'une fonction d'éclairage.